The Influence of Eco-Control, Company Size, Environmental Performance on Sustainability Reporting Disclosure : Case Study on Agricultural Sector Companies listed on the Indonesia Stock Exchange for the period 2018-2022 - Nuraeni, Nuraeni; Sujaya, Fista Apriani; Nasihin, Ihsan (West Science Accounting and Finance, 2024)
Sustainability reporting in Indonesia has become a mandatory report published by financial institutions and public companies listed on the Indonesia Stock Exchange. Obligations related to sustainability reporting refer to Statement of Financial Accounting Standards (PSAK) No.1 Revised 2019, namely that companies are required to disclose additional reports related to environmental life. Under the Global Reporting Initiative (GRI) 2021 standards, the information on a company's applicant list can build stakeholder trust, maintain reputation, increase company value and demonstrate company accountability. Factors that can encourage disclosure of sustainability reporting are Eco-control, company size and environmental performance. One industry that is closely related to the environment and natural resources is the agricultural industry, apart from having a positive impact, there are also negative impacts that also cause harm to the environment. The sample in this research is agricultural sector companies listed on the IDX for 2018-2022. The research uses multiple linear analysis methods with SPSS 23 statistical software. After testing the hypothesis, the results obtained are that Eco-control has a positive influence on sustainability reporting disclosures, while the company size variable has no influence on sustainability reporting disclosures, starting with the environmental performance variable. .